Estimasi Sumberdaya Batubara dengan Menggunakan Metode Cross Section di Pit 2 PT. Tambang Bukit tambi. Site Padang Kelapo. Kec. Muaro Sebo Ulu. Kab. Batanghari. Provinsi Jambi - Calvin Maharza; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. PT. Tambang Bukit Tambi is a mining company which currently has been drilling to obtain coal distribution data and the amount of coal available. The drilling was carried out in an area of 50.8 hectares with 14 drill holes. To find out the amount and distribution of coal. resource estimation is needed. Modelling of 3D coal distribution and coal volume calculation can be use as consideration for mining. Estimation of resources and reserves of minerals important for ease of exploitation commercially of deposits of minerals, because the resources and reserve estimation results can determine investment and estimates the time required by the company in carrying out mine business This research uses cross setion method for calculating of coal volume and coal tonnage, with the help of image processing software that is minescape 4.11.9. the estimation must be made based on the number of blocks that are available after being corrected to the topographic limit. The total coal tonnage obtained in the study area is 3.360.240 tons and Overburden is 4.317.300 bcm. with 1.2 bcm/ton stripping ratio.Keywords : Estimation. Sumberdaya. Ordinary Kriging. variogram. CoalAbstract. PT. Tambang Bukit Tambi is a mining company which currently has been drilling to obtain coal distribution data and the amount of coal available. The drilling was carried out in an area of 50.8 hectares with 14 drill holes. To find out the amount and distribution of coal. resource estimation is needed. Modelling of 3D coal distribution and coal volume calculation can be use as consideration for mining. Estimation of resources and reserves of minerals important for ease of exploitation commercially of deposits of minerals, because the resources and reserve estimation results can determine investment and estimates the time required by the company in carrying out mine business This research uses cross setion method for calculating of coal volume and coal tonnage, with the help of image processing software that is minescape 4.11.9.. the estimation must be made based on the number of blocks that are available after being corrected to the topographic limit. The total coal tonnage obtained in the study area is 3.360.240 tons and Overburden is 4.317.300 bcm. with 1.2 bcm/ton stripping ratio.Keywords : Estimation. Sumberdaya. Ordinary Kriging. variogram. Coal